PENGARUH REINFORCEMENT POSITIF DAN NEGATIF TERHADAP MOTIVASI BELAJAR SISWA KELAS 5 SDN SERUA 01 KOTA TANGERANG SELATAN - Surya Nanda Situmorang; Bambang Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of student learning motivation due to the lack of student interest in learning materials, lack of understanding and lack of student self-confidence. In this case, educators can provide positive and negative reinforcement to students to increase the learning motivation of grade 5 students of SDN Serua 01, South Tangerang City. The purpose of this study was to determine whether there was an influence of positive and negative reinforcement on student learning motivation. This research was conducted at SDN Serua 01, South Tangerang City. The population used in this study were grade VA students and the sample used was 60 students. The instrument given was a questionnaire with a total of 50 statement items. This research was conducted using a descriptive quantitative research method. The data collection technique used in this study was a questionnaire and documentation. The results of the calculations based on this study indicate that there is an influence of positive and negative reinforcement on student learning motivation. This is evident from the results of the calculation of the coefficient of determination which shows a value of 43% on learning motivation and 55.7% is influenced by other external factors.